2007
DOI: 10.1007/s11517-007-0276-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular potassium transport in computer models of the ischemic zone

Abstract: Ischemic heart disease is associated with large mortality and morbidity. Understanding of the relations between coronary artery occlusion, geometry of the ischemic region, physiology of ischemia, and the resulting changes in electrocardiogram (ECG) leads and catheter signals is important to support diagnosis and treatment. Computer models play an important role in understanding ischemia, by linking experimental to clinical results. In this paper we argue that the observed transport of extracellular potassium s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 52 publications
1
12
0
1
Order By: Relevance
“…Potse et al used a one-dimensional (1D) diffusive model for K + ions to establish the spatial profile of [K + ] o across the BZ. 69 The results predict a non-linear [K + ] o spatial evolution within the BZ, showing a steep rise in the BZ adjacent to the NZ and a more flattened behaviour near the CIZ. The authors demonstrate that the diffusion constant which would be needed to explain the experimentally observed profile of K + in the BZ is too large, suggesting that physical diffusion is not the only 5 mechanism that plays a role in the establishment of the BZ.…”
Section: Modelling Border Zone Gradientsmentioning
confidence: 85%
“…Potse et al used a one-dimensional (1D) diffusive model for K + ions to establish the spatial profile of [K + ] o across the BZ. 69 The results predict a non-linear [K + ] o spatial evolution within the BZ, showing a steep rise in the BZ adjacent to the NZ and a more flattened behaviour near the CIZ. The authors demonstrate that the diffusion constant which would be needed to explain the experimentally observed profile of K + in the BZ is too large, suggesting that physical diffusion is not the only 5 mechanism that plays a role in the establishment of the BZ.…”
Section: Modelling Border Zone Gradientsmentioning
confidence: 85%
“…The limited attempts at simulating the spatial temporal evolution of ionic gradients across the ischemic BZ have largely uncoupled the movement of ions and the electric field. Potse et al, [18] demonstrated that measured gradients across an ischemic BZ could be simulated using a model of diffusion coupled to a source term. The spatially varying gradient could then be included as a boundary condition to models of transmembrane current in the bidomain equations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous models of electrophysiology during acute regional ischemia have simulated the effects of these spatial gradients but have not simulated their time evolution [15][17]. More recent work has simulated the time evolution of gradients [18], but have not considered other ionic gradients, the effects of nonlinear interactions between and other ions, the effect of diffusion in the intracellular space or the effects of potential gradients on ion diffusion.…”
Section: Introductionmentioning
confidence: 99%
“…Cependant, certains problèmes ne peuvent être abordés qu'avec un modèle qui représente les flux ioniques provenant des myocytes et qui incorpore leurs interactions avec les flux circulant dans le milieu extracellulaire cardiaque et dans le torse. Cela est vrai pour les maladies affectant les canaux ioniques ou pour comprendre la genèse d'arythmies survenant en bordure d'une région ischémique où l'absence de perfusion altère la composition ionique des milieux intra et extracellulaires et l'état des myocytes [22]. Actuellement, seules de petites préparations permettent de représenter tous les myocytes et la microstructure du tissu cardiaque.…”
Section: Modèle Coeur-torse Et La Reproduction De L'ecgunclassified